The impact of autism spectrum disorder symptoms on gesture use in fragile X syndrome and Down syndrome. (December 2017) - Lorang, Emily; Sterling, Audra; ,
Background & aims: This study compared gesture rate and purpose in participants with Down syndrome and fragile X syndrome, and the impact of autism spectrum disorder symptoms on each syndrome. Methods: Twenty individuals with fragile X syndrome and 20 individuals with Down syndrome between nine and 22 years of age participated in this study. We coded gesture rate and purpose from an autism spectrum disorder evaluation, the Autism Diagnostic Observation Schedule – Second Edition. Results: We did not find between-group differences (Down syndrome compared to fragile X syndrome) in gesture rate or purpose. Notably, as autism spectrum disorder symptoms increased, the group with Down syndrome produced a lower rate of gestures, but used gestures for the same purpose. Gesture rate did not change based on autism spectrum disorder symptoms in the participants with fragile X syndrome, but as autism spectrum disorder symptoms increased, the participants with fragile X syndrome produced a larger proportion of gestures to regulate behavior and a smaller proportion for joint attention/social interaction. Conclusions: Overall, the amount or purpose of gestures did not differentiate individuals with Down syndrome and fragile X syndrome. However, the presence of autism spectrum disorder symptoms had a significant and unique impact on these genetic disorders. In individuals with Down syndrome, the presence of more autism spectrum disorder symptoms resulted in a reduction in the rate of gesturing, but did not change the purpose. However, in fragile X syndrome, the rate of gestures remained the same, but the purpose of those gestures changed based on autism spectrum disorder symptoms. Implications: Autism spectrum disorder symptoms differentially impact gestures in Down syndrome and fragile X syndrome. Individuals with Down syndrome and more autism spectrum disorder symptoms are using gestures less frequently. Therefore, clinicians may need to consider children with Down syndrome demonstrating symptoms of autism spectrum disorder as distinctly different from children with Down syndrome and few to no symptoms of autism spectrum disorder when implementing interventions or therapy techniques. Severity of autism spectrum disorder symptoms in fragile X syndrome affects qualitative gesture use and motivation to communicate through social gestures, which may be an appropriate goal to target in children with fragile X syndrome and heightened autism spectrum disorder symptoms.